Low Dose Theophylline Showed an Inhibitory Effect on the Production of IL-6 and IL-8 in Primary Lung Fibroblast from Patients with COPD - Jing Zhang; Ming-xiang Feng; Jie-ming Qu (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is characterized by the abnormal and chronic lung inflammation. We hypothesized that lung fibroblasts could contribute to the local inflammation and investigated whether low dose theophylline had a beneficial effect on fibroblasts inflammation. Subjects undergoing lobectomy for bronchial carcinoma were enrolled and divided into COPD and control groups according to spirometry. Primary human lung fibroblasts were cultured from peripheral lung tissue distant to tumor tissue. There was a significant increase in both the mRNA expressions and protein levels for IL-6 and IL-8 in fibroblasts in COPD group, and the values were negatively correlated with lung function (P<0.05). For COPD fibroblasts, the protein levels of IL-6 and IL-8 decreased from 993.0 ± 738.9 pg/mL to 650.1 ± 421.9 pg/mL (P=0.014) and from 703.1 ± 278.0 pg/mL to 492.0 ± 214.9 pg/mL (P=0.001), respectively, with 5 μg/mL theophylline treatment. In addition, theophylline at the dose of 5 μg/mL reduced the increased production of IL-6 and IL-8 induced by 1 μg/mL LPS in primary human lung fibroblasts. Our data suggest that lung fibroblasts participate in the chronic inflammation in COPD by releasing IL-6 and IL-8, and low dose theophylline can alleviate the proinflammatory mediators’ production by fibroblasts.